HSG with Laparoscopic Correlation in Infertility Patients: An Observational Study - Dubbewar, Avinash; Nath, Saumen Kanti; Hiremath, Ravishekar N.; Ghodke, Sandhya; Gouru, Prathyusha; Yadav, Preeti (Perspective of Recent Advances in Medical Research Vol. 11, 2023)
Uterine abnormalities account for 10% of infertility cases and 50% of women who experience recurrent early pregnancy loss, while fallopian tube abnormalities account for 20% of such cases. HSG was performed on 61 infertility and subfertility patients who were undergoing evaluation and treatment at our centre. A total of 25 patients from this group underwent diagnostic laparoscopy, and their results were retrospectively correlated with HSG findings. All of the patients included in the study had either primary or secondary infertility. There were 49 primary infertility patients and 12 secondary infertility patients among the 61 infertility patients. Patients ranged in age from 23 to 35 years. The average duration of primary infertility was 5 years, and 3.5 years for secondary infertility. Total 61 patients underwent HSG, 42(68.8%) patients had normal findings and 19(31.14%) patients had abnormal findings. In abnormal findings 4(6.55%) were Mullerian abnormalities and 15(24.59%) were either unilateral or bilateral tubal block. Total 25 patients underwent diagnostic laparoscopy out of 61 patients. The sensitivity of HSG was 90% and specificity was 60 % with positive predictive value of 60% and negative predictive value of 90% as compared to diagnostic laparoscopy. Peri-adnexal adhesions were discovered in 5 (20%) of the obstructed tubes during our laparoscopic examinations. One (4%) of the blocked tubes had endometriosis, and two (8%) had probable intra-tubal block. In 3 (12%) cases, pelvic inflammatory illness was discovered to be a factor. In our study, HSG demonstrates high sensitivity. As a result, it should be used as the first step in determining uterine abnormality and tubal patency. Because the specificity is low, we believe that laparoscopy is required to identify cases of tubal block that were missed or incorrectly identified on HSG. Furthermore, in patients who were found to have tubal block on HSG, laparoscopy assists in determining the cause of infertility, such as the presence of peritubal adhesions and endometriosis, which can guide appropriate therapy.